The Relevance of Maqashid Syari'ah in Determining the Age Limit for Marriage: A Study of the Implementation of Law No. 16 Years 2019 - Syahputri Hutabarat; Imam` Yazid; Fatimah Zahara (Universitas KH. Abdul Chalim Mojokerto, 2025)
Determination of the marriage age limit through Law No. 16 of 2019 reflects progressive steps in protecting children's rights and preventing the negative impacts of early marriage. This study aims to analyze the relevance of maqashid sharia in supporting this policy, especially in maintaining the five main principles: protection of religion (hifz al-din), soul (hifz al-nafs), reason (hifz al-'aql), descendants (hifz al-nasl), and property (hifz al-mal). With a normative approach and qualitative analysis of Islamic legal literature and related legal documents, this research reveals that a higher marriage age limit is in line with the Sharia goal of ensuring the welfare of individuals and society. Apart from that, the implementation of Law No. 16 of 2019 is faced with challenges, such as cultural resistance and lack of legal awareness, which require educational strategies and strengthening regulations. This study provides practical recommendations for policy makers to align maqashid sharia with the implementation of the law, to support quality and sustainable family development.